Adverse Pregnancy Outcomes and Prognostic Factors in Hepatitis B Virus Patients with Intrahepatic Cholestasis During Pregnancy - Chong Zhang; Hong Wei; Zhiqiang Zhao; Yunxia Zhu (IMR Press, 2024)
Background: We conducted this study to investigate adverse pregnancy outcomes of hepatitis B virus infection coexistng with intrahepatic cholestasis in pregnant women, along with identifying associated risk factors. Methods: We retrospectively collected study data from Beijing Youan Hospital in China spanning January 2014 to December 2021. The study included 220 patients, divided into two groups: Group I consisted of 110 patients with hepatitis B virus infection and intrahepatic cholestasis during pregnancy, while Group II comprised 110 patients with hepatitis B virus infection alone. Maternal demographics, laboratory values, obstetric complications, and adverse pregnancy outcomes were collected and analyzed between Groups I and II. To investigate the features of hepatitis B virus infection with intrahepatic cholestasis in pregnancy patients further, we also evaluated risk factors of adverse pregnancy outcomes in Group I. Results: Adverse pregnancy outcomes, including preterm birth (<37 weeks (w)), postpartum hemorrhage, meconium-stained amniotic fluid, neonatal asphyxia, neonate intensive care unit admission and small for gestational age rates were significantly increased for Group I compared with Group II (p < 0.05). In hepatitis B virus infection patients with intrahepatic cholestasis during pregnancy, elevated total serum bile acids independently correlated with six adverse pregnancy outcomes. Conclusions: Pregnant patients with both hepatitis B virus infection and intrahepatic cholestasis experienced a higher occurrence of adverse pregnancy outcomes compared to those with Hepatitis B virus infection alone. Total serum bile acids were an independent risk factor for adverse pregnancy outcomes in Hepatitis B virus infection with intrahepatic cholestasis during pregnancy. Clinical Trial Registration: The study was registered with https://classic.clinicaltrials.gov/ (no.: zx10201201).